Molecular Dynamic Simulations Of Mlac Inhibition By Antibiotic In Escherichia Coli - Umairah Ramli; Muhamad Arif Mohamad Jamali; Ismatul Nurul Asyikin Ismail; Fatin Hilyani Mohamad; Liyana Azmi (Malaysian Society for Biochemistry and Molecular Biology, 2024)
Malaysian Journal of Biochemistry and Molecular Biology Special Issue Page (55-62)